Posterior quadratus lumborum block for primary total hip arthroplasty analgesia: a comparative study - Kukreja, Promil (Einstein (Sao Paulo), 2019)
OBJECTIVE: To compare analgesia and opioid consumption for patients undergoing primary total hip arthroplasty with preoperative posterior quadratus lumborum block with patients who did not receive quadratus lumborum block. METHODS: The medical records of patients undergoing unilateral total hip arthroplasty between January 1st, 2017 and March 31, 2018 were reviewed, and 238 patients were included in the study. The primary outcome was postoperative opioid consumption in the first 24 postoperative hours. Secondary outcomes were intraoperative, post anesthesia care unit, and 48-hour opioid consumption, postoperative pain Visual Analog Scale scores, and post-anesthesia care unit length of stay. Primary and secondary endpoint data were compared between patients undergoing primary total hip arthroplasty with preoperative posterior quadratus lumborum block with patients who did not receive quadratus lumborum block. RESULTS: For the patients who received quadratus lumborum block, the 24-hour total oral morphine equivalent (milligram) requirements were lower (53.82mg±37.41), compared to the patients who did not receive quadratus lumborum block (77.59mL±58.42), with p=0.0011. Opioid requirements were consistently lower for the patients who received quadratus lumborum block at each additional assessment time point up to 48 hours. Pain Visual Analog Scale scores were lower up to 12 hours after surgery for the patients who received a posterior quadratus lumborum block, and the post-anesthesia care unit length of stay was shorter for the patients who received quadratus lumborum block. CONCLUSION: Preoperative posterior quadratus lumborum block for primary total hip arthroplasty is associated with decreased opioid requirements up to 48 hours, decreased Visual Analog Scale pain scores up to 12 hours, and shorter post-anesthesia care unit length of stay. Level of evidence: III